The Influence of Fundamental Factors, Economic Value Added, Market Value Added on Stock Returns: Firm Value as a Mediating Variable - Sari, Silvia; Lusiana, Lusiana (UPI YPTK Journal of Business and Economics, 2024)
This study aims to determine the effect of fundamental factors, economic value added, market value added on stock returns and firm value as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period, and there are as many as 335 companies. The sample in this study was determined using a purposive sampling technique with a total of 44 companies. The analytical method used is multiple linear regression analysis with the help of the SPSS program. The results of this study are Fundamental Factors, EVA, and MVA have a significant effect on Stock Return. Fundamental factors partially have a significant effect on firm value. EVA partially has no significant effect on firm value. MVA partially has no significant impact on firm value. Firm value partially has a significant effect on firm value. Fundamental factors partially have a significant effect on Stock Return through Firm value as a Mediating variable. EVA partially has no significant impact on stock return through firm value as a mediated variable. MVA partially has a significant effect on stock return through firm value as a mediated variable.